STRATEGI PENERJEMAHAN DALAM BUKU KEMBALINYA SURGA YANG HILANG (SEBUAH EPOS LAHIRNYA BANGSA INDONESIA) TERJEMAHAN ‘AUDATUL FIRDAUS KARYA ALI AHMAD BAKATSIR - Intan Rohmawati; Nailur Rahmawati (Universitas Negeri Semarang, 2022)
In an effort to add insight and knowledge and open the mind about the Arab world, one of them is by reading Arabic literature. One of the works of Arabic literature is 'Audatul Firdaus, a play written by an Egyptian writer named Ahmad Ali Bakatsir. This research is a type of qualitative descriptive research. The data on this study is in the form of words, phrases, or sentences contained in the book 'Audatul Firdaus and its translation entitled Kembalinya Surga yang Hilang (Sebuah Epos Lahirnya Bangsa Indonesia). Based on the results of the analysis of translation strategies in the book Kembalinya Surga yang Hilang (Sebuah Epos Lahirnya Bangsa Indonesia) translation 'Audatul Firdaus there are 6 types of translation methods, 5 translation procedures, and 9 translation techniques which are the description of translation procedures according to Newmark. This translation is oriented towards the source language. The use of translation methods that are oriented in the source language even reaches 75%. The most dominant type of method is the literal method. The most dominant type of procedure used is transposition procedure. Differences in Indonesian and Arabic systems require structural adjustments in the translation process. Such adjustments to reconstruct Tsu in Tsa are reasonable. So that the translation can be received by Bsu readers and the message can be delivered. While the most dominant type of technique used is the transfer technique. Transfer techniques are more widely used to translate character names. That is because the type of text analyzed is drama text so many write the name of the character in the dialogue.